Leadership Influence on Employee Commitment: A Case Study of the Social Affairs Department - Nofriansyah, Rifki; Ningrum, Tia Ayu; Irsyad, Irsyad; Santoso, Yulianto (Al-Qalam Institue, 2025)
This study investigates the influence of leadership on employee work commitment at the Social Affairs Office of West Sumatra Province. The research aims to assess employee commitment levels, evaluate the leadership quality of the head of the department, and examine the significant effect of leadership on work commitment. Using a quantitative correlational design, the study involved 40 employees selected from a population of 67 through proportional random sampling. Data were collected via a Likert-scale questionnaire, preceded by a pilot test with 20 employees. Analysis using SPSS 27 revealed that employee commitment was high (88%) and leadership performance was good (85%). The correlation coefficient between leadership and work commitment was 0.392, indicating a significant positive relationship. The coefficient of determination showed that leadership accounted for 39.2% of the variance in work commitment. These findings highlight the substantial role of effective leadership in enhancing employee commitment within public sector organizations, particularly in the Social Affairs Office of West Sumatra Province.